Health culture in the Baghdadi community: an analytical anthropological view of Baghdadi proverbs - Khalaf, Shalal (Al-Adab Journal, 2023)
The current research aims to identifyRecognizing the image of health culture in the light of the popular Baghdadi proverbsDirecting our gaze to the popular Baghdadi proverbs that we can benefit fromExamination of the raw material, which is the many and varied examplesThe research was based on the method of analyzing the scientific material to be studied (Al-Baghdadi Proverbs)The research reached to the most important resultsFolk proverbs are a means of delivering a message in the field of healthy culture to individuals that helps them to know a lot of information about the spread of diseases and limit their confrontation.Popular proverbs for any society express the intellectual system that forms the cultural framework for them